Event of signature : Jacques Derrida and repeating the unrepeatable - Fisěrová, Michaela (Albany : SUNY Press, 2022)
"In dialogue with Derrida, formulates a new philosophical problem - a complex aporia that underlines the topic of the handwritten as a sign of legal identification" --
Chapter IV. Deconstructing Handwritten Signature I -- Aporia of Natural Resemblance -- Spectral Resemblance -- Chapter V. Deconstructing Handwritten Signature II -- Aporia of Authentic Tracing -- Disseminated Tracing -- Chapter VI. Deconstructing Handwritten Signature III -- Aporia of Identical Repetition -- Iterated Repetition -- Chapter VII. Event of Manual Signing: On Repeating of the Unrepeatable -- Event Trapped in Interpretation -- Event Trapped in Representation -- The Event of Iteration -- Postscript -- Notes -- Bibliography -- Name Index -- Subject Index
Description based upon print version of record.
Includes bibliographical references and indexes.
JSTOR
Keywords: Signatures (Writing) -- Philosophy; Signature (Law) -- Philosophy; Signatures -- Philosophie; Signature (Droit) -- Philosophie; PHILOSOPHY / Movements / Deconstruction; Electronic books